An evaluation of application of information technology and communication of learning science with the theme of solar system - Septiana Indri Hapsari; Kristian Handoyo Sugiyarto; Naoko Kosaka (Research and Social Study Institute, 2018)
This study aimed to determine (1) the readiness of teacher in applying ICT of science learning, (2) the level according to the application of ICT in the implementation of science learning, (3) the level of completeness of learners after applying ICT in science learning. This evaluation research use the Countenance Stake model that are Antencedent (input), Transaction (process), and Outcomes (output). Respondents involved in this study were Science teachers and students in Junior High School in Yogyakarta that consists of SMPN 5, SMPN 8, SMPN 15, and SMP Pangudi Luhur 1 Yogyakarta.Data collection techniques using purposive sampling using the instrument observation sheets, questionnaires teachers, questionnaires learners interview guidelines and checklist documents RPP. Data were analyzed using a quantitative approach to the t-score, anda qualitative approach descriptively.The results of this study are (1) the preparation of teachers in applying ICT is still not optimal. (2) the suitability of the use of ICT in the learning process quite well, it was shown that on average the suitability of the use of ICT 48,24% at a preliminary stage, 53,21% on core activities. 47,20% at the closing, and 36,74% in the assessment of the range of 56-68%, (3) learning Outcomes are still unsatisfactory ie 62,72% of the normal standard of 70%.